Freedom, coice and achieving self-realisation in the dystopian world of Parable of the Talents by Octavia Butler - Rezaei, Zahra; Bahar, Ida Baizura; Abdullah Mohan, Zahraa (Australian International Academic Centre, 2022)
This study examines how the American science fiction author Octavia Butler (1947-2006) reflects the issue of how Olamina, the protagonist of Parable of the Talents (1998), attempts to establish a new religion, Earthseed, while changing her dystopian world. Butler is a distinguished novelist who brings to light the narrative on human life and challenges in a society where individuals are treated with discrimination and deprived of their rights, freedom, and independence, and takes a serious note of these topics by offering a representative portrait of the American society through her fiction. Here, we explore issues of human freedom, choice and self-realisation in a civil society by utilising a novel combination of the concepts of freedom and choice by John Rawls and Isaiah Berlin as well as self-realisation by Karl Marx as the fundamental elements to examine Olamina’s belief, attitude and the act of making choices. Our findings reveal that Olamina becomes an assertive and independent woman through two stages of self-realisation, namely self-actualisation and self-externalisation: she finds her voice, succeeds in challenging her ideological social system and, at last, successfully spreads her new philosophical ideas to another part of the world. Through our original methodology of combining the concepts of freedom, choice and self-realisation, we found that Butler has skillfully depicted the social and technological evolutions which have caused the futuristic dystopias in 2030s California, and further illustrates the ways that characters can confront these changes if given the freedom and the autonomy to act and change their oppressive existence.